Then comes seduction - Balogh, Mary (New York Dell, 2009)
In a night of drunken revelry, Jasper Finley, Baron Montford, gambles his reputation as London's most notorious lover on his ability to seduce the virtuous Katherine Huxtable. For Katherine, Jasper's offer is irresistible: to make London's most dangerous rake fall in love with her. Then Jasper suddenly ups the ante by asking her to become his wife.
Second in a series of novels about the Huxtable family, prececed by Vanessa's story, "First comes marriage," and now Katherine's story, in this work, "Then comes seduction." Margaret's story will follow, "At last comes love," and Stephen's story, "Seducing an angel." -- Cover, p.2.
Keywords: Aristocracy (Social class) -- England -- Fiction; Marriage -- England -- Fiction; Regency fiction; Love stories